Wood gas as engine fuel (FAO RomeIT, 1986)
Presents summary of modern wood gasification technology. Discusses possibilities for fuelling different types of engines by producer gas; gasification fuels; and gasifier types and design rules. Examines the economics of the application of wood gasification technology to internal combustion engines including those of modern vehicles. Gives accounts of recent operating experiences. Discusses the future of wood gas as engine fuel and emphasizes the need for continued international cooperation in this field.
Bibliography: p. 170-173